Mosaic : [compact disc, unabridged] : pieces of my life so far - Grant, Amy (Brilliance Audio, 2007)
"Rendered with the lyrical insight we see in her music, Amy reflects on the pieces of her life through the years, forming a vivid mosaic of memories rich in color, varied in texture, and united in their heartfelt design"--Container.